Advanced Robotic Angiography Systems for Image Guidance During Conventional Transarterial Chemoembolization: Impact on Radiation Dose and Image Quality. Issue 3 (March 2019) - Vogl, Thomas J.; Alizadeh, Leona S.; Maeder, Richard; Naguib, Nagy N.; Herrmann, Eva; Bickford, Matthew W.; Burck, Iris; Albrecht, Moritz H.
Abstract : Objectives: The aim of this study was to compare 2 advanced robotic angiography systems for real-time image guidance in terms of radiation dose and image quality (IQ) during conventional transarterial chemoembolization (C-TACE) of hepatic malignant tumors. Materials and Methods: One hundred six patients (57 women/49 men; mean age, 60 ± 11 years) who had undergone C-TACE using 2 generations of robotic angiography platforms for image guidance were included in this retrospective study. Patients were divided into 2 groups (n = 53, respectively): group 1 (first generation) and group 2 (second generation). Radiation dose for fluoroscopy and digital subtraction angiography (DSA) was compared between first-generation and second-generation angiography equipment, respectively. Among several features of the second-generation compared with the first-generation system, improvements included a refined crystalline detector system for enhanced noise reduction and advanced CARE filter software for lowering radiation dose. Radiation dose was measured using an ionization chamber. Image quality was assessed by 3 radiologists using 5-point Likert scales. Results: Both groups were comparable in terms of number and location of lesions, as well as body weight, body mass index, and anatomical variants of feeding hepatic arteries (all P > 0.05). Dose-area product (DAP) for fluoroscopy was significantly lower in group 2 (1.4 ± 1.1 Gy·cm 2 ) compared with group 1 (2.8 ± 3.4 Gy·cm 2 ; P = 0.001). For DSA, DAP was significantly lower ( P = 0.003) in group 2 (2.2 ± 1.2 Gy·cm 2 ) versus group 1 (4.7 ± 2.3 Gy·cm 2 ). Scores for DSA IQ indicated significant improvements for group 2 by 30% compared with group 1 ( P = 0.004). Regarding fluoroscopy, scores for IQ were 76% higher in group 2 compared with group 1 ( P = 0.001). Good to excellent interrater agreement with Fleiss kappa coefficients of κ = 0.75 for group 1 and κ = 0.74 for group 2 were achieved. Conclusions: Most recent generation robotic angiography equipment allows for considerable radiation dose reductions while improving IQ in fluoroscopy and DSA image guidance during C-TACE treatment.